Evaluation of the in vitro effects of commercial herbal preparations significant in African traditional medicine on platelets - Mmamosheledi E. Mothibe; Christina P. Kahler-Venter; Elzbieta Osuch (BMC, 2019)
Abstract Background Commercial herbal medicines (CHMs) marketed as immune boosters are gaining wide popularity in South Africa, in the absence of control and regulatory guidelines. These commercially packaged and labelled herbal preparations, acquired in various retail outlets, are used without consulting either a conventional health provider or a traditional health practitioner. Although they are indicated for immune-boosting purposes, they might exert many other beneficial and unwanted effects on physiological systems. Platelets are crucial in haemostasis and important for the immunological system. The aim was to investigate the effect of the CHMs used to strengthen the immune system on the activity of human platelets. Methods Six CHMs commonly used as African traditional medicines in Pretoria, South Africa, were tested for their effects on healthy, isolated human platelets, using a bioluminescence method. The tested herbal medicines were Intlamba Zifo™, Maphilisa™ Herbal medicine, Matla™ African medicine for all diseases, Ngoma™ Herbal Tonic Immune Booster, Stametta™ Body Healing Liquid, and Vuka Uphile™ Immune Booster and serial-diluted standards of each from 10 to 10,000 times. The luminol-enhanced luminescence activity of the platelets was measured after incubation with the herbal medicines and activation with phorbol myristate acetate (PMA) or N-formyl-methionyl-leucyl-phenylalanine (fMLP). Results Five herbal medicines, namely Intlamba Zifo™, Maphilisa™ Herbal medicine, Matla™ African medicine for all diseases, Stametta™ Body Healing Liquid, and Vuka Uphile™ Immune Booster exerted comparable weak inhibitory effects on both PMA and fMLP-induced platelets, which were concentration dependent at high doses, and inversely related to concentration at low doses. Intlamba Zifo™, Matla™ African medicine for all diseases, Stametta™ Body Healing Liquid, and Vuka Uphile™ exhibited weak, but non-systematic stimulatory effects at low doses, which were not statistically significant. Ngoma™ Herbal Tonic Immune Booster had weak, inhibitory effects at high doses and weak stimulatory effects that were inversely related to concentration at low doses. Conclusion The findings suggest a potential beneficial role of the CHMs in the suppression of platelets' reactivity and in enhancing the immune system. Caution, however, should be exercised as platelet inhibition and stimulation predispose to the risk of bleeding and thrombosis, respectively.